ASSESSMENT OF THE NEEDS OF FAMILIES RAISING CHILDREN WITH DISABILITIES IN THE PRACTICE OF THE UKRAINIAN NON-GOVERNMENTAL ORGANIZATIONS - Shved, Olha; Tkach, Iryna (The Modern Higher Education Review, 2021)
Social services in Ukraine are still in the process of formation and development. It is necessary to significantly improve the quality of social services, modernize the funding mechanisms, and expand the range of possible providers of these services. Families raising children with disabilities need special services and attention not only from government agencies, but also from non-governmental organizations (NGOs), which are increasingly supporting them. The study was conducted in Ukraine and had several objectives: 1. To find out whether NGOs work with families with children with disabilities; 2. If so, do they assess the needs of families and children with disabilities; 3. What methods are best to use when assessing needs?